Efficiency of supervised farm practice work in twenty-two departments of vocational agriculture near Reynolds, Illinois - Robinson, R. O., author; Mondart, Clifford L., advisor; Schmidt, Gustavus Adolphus, 1880-, committee member; Clark, Andrew Giles, committee member; Betts, Gilbert L., committee member; Kezer, Alvin, 1877-, committee member (Colorado State University. Libraries, 1940)
To view the abstract, please see the full text of the document.
Keywords: Agriculture -- Study and teaching